The Helpmekaar : rescuing the "volk" through reading, writing and arithmetic, c. 1916-c. 1965 (Historia, 2021)
his article looks at the establishment and shifting role of the Helpmekaar Society of the Cape Province as welfare catalyst, set up in the aftermath of the Rebellion of 1914-15. Driven by Afrikaner ethnic nationalist motives - it set itself two goals. The immediate aim was to save Afrikaner rebels and their families from financial ruin. The second objective was complicated and changing: to promote the general development, upliftment and welfare of the Dutch-speaking section of the South African population and to develop a distinctive Afrikaans culture. The paper concentrates on the evolution of the second goal into a sharp educational focus aimed at unlocking the potential of Afrikaner youth as a solution to the poor white problem. Because the Helpmekaar was shaped by ideologies of class and race, this analysis engages with a couple of existing historiographical conversations about poor whites, the state, welfarism and also provides a revealing lens into the politics of white education itself. Despite the Helpmekaar's sectional ethnic and racial focus and the accompanying socio-political engineering, it acted as a welfare catalyst that contributed significantly - financially and as lobbyist for educational causes - in effecting educational change; in this regard it benefited a far wider community than was originally intended.  Die artikel ontleed die bydrae van die Helpmekaarverening van die Kaapprovinsie as welsyns katalisator in die ekonomiese opheffing van Afrikaners in die vaarwater van die Rebellie van 1914-15. Die Helpmekaar het 'n tweeledige doelwit beoog. Eerstens om Afrikaner rebelle en hul gesinne van ekonomiese ondergang te red. Die tweede doel was meer gekompliseerd: die bevordering van die algemene ontwikkeling en welsyn van die Hollandssprekende deel van die Suid-Afrikaanse bevolking met die fokus op die ontwikkeling van 'n spesifieke Afrikaanse kultuur. Die artikel fokus op die ontwikkeling van die tweede doelstelling in 'n spesifieke opvoedkundige fokus, naamlik om die arm blanke probleem deur die ontsluiting van die potensiaal van die Afrikanerjeug deur opvoeding, op te los. Die Helpmekaar is gevorm deur ideologiee van ras en klas. Die artikel sluit dus aan by 'n aantal bestaande historiografiese debatte oor arm blankes, die welsynstaat, en verskaf ook insae in die politiek van wit onderwys. Ten spyte van sy eng etniese en nasionalistiese fokus en die gepaardgaande sosiale ingenieurswese het die Helpmekaar deur sy finansiele bydraes en as kampvegter vir opvoedkundige sake 'n beduidende rol in die bevordering van onderwys en opvoeding gespeel wat 'n veel wyer gemeenskap as wat aanvanklik beoog is, bevoordeel het.
Keywords: Etniese mobilisering; Rebellie van 1914-15; Helpmekaarbeweging; Welfare; Education; Ethnic mobilisation; ACVV